Socioeconomic Disparities in Hospital Utilization Among Female Workers in Indonesia: A Cross-Sectional Study - Ratna Dwi Wulandari; Agung Dwi Laksono; Yoyok Bekti Prasetyo; Nurhasmadiar Nandini (SAGE Publishing, 2022)
Background: The study aims to analyze the relationship between socioeconomic and hospital utilization among female workers in Indonesia. Methods: The study analyzed secondary data from the 2018 Indonesian Basic Health Survey. The study gathered 161 186 female workers through stratification and multistage random sampling. As control factors, the study looked at age, marital status, education, occupation, and health insurance, in addition to the categories of socioeconomic and hospital utilization. The study used binary logistic regression to evaluate the data in the final step. Results: The result shows female workers with poorer wealth status are 1.142 times more likely than the most impoverished female workers to utilize the hospital (AOR 1.142; 95% CI 1.135-1.148). Female workers with median wealth status are 1.509 times more likely than the poorest female workers to take advantage of the hospital (AOR 1.509; 95% CI 1.501-1.517). Female workers with wealthier wealth status are 1.808 times more likely than the poorest female workers to use the hospital (AOR 1.808; 95% CI 1.799-1.817). The wealthiest female workers are 2.399 times more likely than the poorest female workers to utilize the hospital (2.399; 95% CI 2.387-2.411). Conclusion: The study concluded a relationship between socioeconomic status and hospital utilization among female workers in Indonesia. The better the socioeconomic, the better the hospital utilization.